Identification of somatic hypermutations in the TP53 gene in B-cell chronic lymphocytic leukemia - Malčíková, Jitka; Šmardová, Jana; Peková, Soňa; Čejková, Soňa; Kotašková, Jana; Francová, Hana; Tichý, Boris; Doubek, Michael; Brychtová, Yvona; Janek, Daniel; Pospíšilová, Šárka; Mayer, Jiří; et al. (Molecular immunology, 2008)
Abnormalities of the TP53 gene are associated with a particularly severe prognosis in patients with B-cell chronic lymphocytic leukemia (B-CLL). This tumor-suppressor is mostly inactivated by the deletion of one and point mutation of the other allele and has not been previously shown to be hypermutated in B-CLL. We identified two patients whose lymphocytes showed repeatedly an extensive proportion of TP53 mutated cells by FASAY analysis (the yeast functional assay) and harbored various TP53 mutations, mostly single-base substitutions, in individual cells. The mutation targeting exhibited characteristic traits of the somatic hypermutation process. In the first patient (harboring the unmutated IgVH locus) a significant bias to point mutations at CG pairs (21/25; P=0.009), their remarkable preference for the RGYW/WRCY motives (28%) and the highest expression of the activation-induced cytidine deaminase (AID) mRNA among the 34 tested B-CLL samples. In the second patient no CG bias was observed but the targeting of point mutations into the RGYW/WRCY motives was even more prominent here (7/16; 44%). Moreover, six out of eight point mutations affecting AT pairs were localized in the WA/TW motives, which are also characteristic for the somatic hypermutations. This patient, who was IgVH-mutated, already did not express any significant amount of the AID transcript. Our findings add a new aspect to the mosaic of the p53 mutability in B-CLL.
Keywords: mutace; Cytidine Deaminase; financování organizované; Lymphocytes; Financing, Organized; Leukemia, Lymphocytic, Chronic, B-Cell; geny p53; lidé; lymfocyty; Point Mutation; Genes, p53; Somatic Hypermutation, Immunoglobulin; somatická hypermutace imunoglobulinových genů; Mutation; chronická lymfatická leukemie; cytidindeaminasa; bodová mutace; Humans